Application of deontic logic in role-based access control - Kołaczek, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a short overview of the foundations of the Role-Based Access Control Modal Model and its properties. In particular, the translation of these model formulae to the first-order logic formulae in a form of Horn's clauses is analysed. The automation of processes and mechanisms related to access control on the basis of logical automated reasoning and the PROLOG language are described.
Keywords: formal logic; access control; RBAC; system security; reasoning automation